2019
DOI: 10.1136/bmjresp-2018-000397
|View full text |Cite
|
Sign up to set email alerts
|

Safety and survival data in patients with idiopathic pulmonary fibrosis treated with nintedanib: pooled data from six clinical trials

Abstract: IntroductionNintedanib slows disease progression in patients with idiopathic pulmonary fibrosis (IPF) by reducing the rate of decline in forced vital capacity, with an adverse event profile that is manageable for most patients. We used data from six clinical trials to characterise the safety and tolerability profile of nintedanib and to investigate its effects on survival.MethodsData from patients treated with ≥1 dose of nintedanib 150 mg two times per day or placebo in the 52-week TOMORROW trial and/or its op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(119 citation statements)
references
References 24 publications
9
98
0
12
Order By: Relevance
“…Nintedanib reduced the rate of decline in FVC both in patients who were and were not receiving mycophenolate at baseline, with a numerically greater treatment effect in patients who were not taking mycophenolate. The adverse event profile of nintedanib was similar to that previously observed in patients with IPF, being characterized mainly by gastrointestinal events, particularly diarrhea of mild or moderate severity [56]. The efficacy and safety of nintedanib in patients with progressive fibrosing ILDs have also been assessed in the INBUILD® trial.…”
Section: Nintedanibsupporting
confidence: 59%
“…Nintedanib reduced the rate of decline in FVC both in patients who were and were not receiving mycophenolate at baseline, with a numerically greater treatment effect in patients who were not taking mycophenolate. The adverse event profile of nintedanib was similar to that previously observed in patients with IPF, being characterized mainly by gastrointestinal events, particularly diarrhea of mild or moderate severity [56]. The efficacy and safety of nintedanib in patients with progressive fibrosing ILDs have also been assessed in the INBUILD® trial.…”
Section: Nintedanibsupporting
confidence: 59%
“…Nintedanib had a similar adverse event profile in patients with mild or moderate impairment in gas exchange in the INPULSIS trials and in patients with more severe disease in the INSTAGE trial, albeit with a greater frequency of serious adverse events in patients with more severe disease, as might be expected in a sicker population. Previous analyses of safety data from clinical trials of nintedanib have shown a consistent safety and tolerability profile across trials and patient subgroups [13,14,23]. Real-world data from clinical practice suggest that the safety and tolerability profile of nintedanib is similar in patients with IPF who have severe disease as in patients with milder disease, but that patients with more severe disease have a higher rate of treatment discontinuation [16,18,24].…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, the current FDA approved anti-fibrotic medications slow the progression of disease but patient-reported symptoms were largely unchanged. Pooled data from the INPULSIS and TOMORROW trials involving nintedanib demonstrated a reduction in acute exacerbations [59] and secondary endpoint analysis with pirfenidone and nintedanib suggest an improvement in all-cause and IPF related mortality [60,61]. These additional benefits need to be confirmed with larger randomized clinical trials.…”
Section: Discussionmentioning
confidence: 99%